Pengaruh Budaya Organisasi Dan Work Engagement Terhadap Kinerja Karyawan - Rochimah Imawati (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2011)
Studies about job performance show that it is influence by many variables. These present study what to test the hypotheses that work engagement and organization culture simultaneously influence job performance. Data were collected among employees at University Al Azhar of Indonesia. The result show that both of the variable, work engagement and organization culture influence job performance but organization culture show better prediction than work engagement.